Determination of the level of chromium (III) and comparison of chemical precipitating agents to recover and reuse it from tannery waste water - Awoke Misganaw; Banchamlak Akenaw; Shegaw Getu (Desalination and Water Treatment)
Most tannery wastes are discharged into the natural environment without any treatment system and pose a potential negative impact on living things due to their high organic loading and chromium content. In this study, a comparison of chemical precipitating agents to recover and reuse chromium (III) from tannery waste water was done. The study was conducted by performing physicochemical characterization and chemical precipitation. The Cr concentration was determined using the flame atomic absorption spectroscopy (FAAS) method. Statistical analysis was performed using the SPSS program through one-way analysis of variance (ANOVA). In terms of sludge volume, magnesium oxide produced 25%, calcium hydroxide 31%, and sodium hydroxide 44%. The findings have implications for global sustainability, as the use of magnesium oxide as a precipitating agent results in a smaller sludge volume and potentially less environmental impact.